Development of quality management systems 'QMS' towards total quality management 'TQM' based on project management 'PM' framework - Safar, Hisham; Bielova, O.I.; Бєлова, Олена Ігорівна (Methuen Publishing House, 2021)
In project management, quality management (QM) means developing and following processes and procedures to ensure that a project satisfies the specified needs of the customer. Planning, scoping, execution and control in all stages of the project. Therefore; QM requires the opportunity to shape and organise a team of individuals in cost effective and time span to reach a qualitative target, which would result in the development of a good quality
Keywords: project management; quality management